2020
DOI: 10.1080/20013078.2020.1786967
|View full text |Cite
|
Sign up to set email alerts
|

The RNA‐binding protein hnRNPU regulates the sorting of microRNA‐30c‐5p into large extracellular vesicles

Abstract: Jansen (2020) The RNAbinding protein hnRNPU regulates the sorting of microRNA-30c-5p into large extracellular vesicles,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 36 publications
1
89
0
Order By: Relevance
“…Although packaging of exRNAs in EVs is known to be a selective process that leads to the enrichment of certain exRNAs in EVs (Cha et al, 2015;Lee et al, 2019;Lin et al, 2019;Lu et al, 2017), the mechanisms by which this packaging occurs is poorly understood. RNA-binding proteins appear to play a major role in this process, likely controlling both stability and sorting of the RNAs (Deng et al, 2020;McKenzie et al, 2016;Santangelo et al, 2016;Shurtleff et al, 2016;Villarroya-Beltri et al, 2013;Zietzer et al, 2020). We and others identified argonaute 2 (Ago2) and other RISC complex proteins as potent mediators of miRNA sorting into EVs (Bukong et al, 2014;Clancy et al, 2019;Mantel et al, 2016;McKenzie et al, 2016;Melo et al, 2014).…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Although packaging of exRNAs in EVs is known to be a selective process that leads to the enrichment of certain exRNAs in EVs (Cha et al, 2015;Lee et al, 2019;Lin et al, 2019;Lu et al, 2017), the mechanisms by which this packaging occurs is poorly understood. RNA-binding proteins appear to play a major role in this process, likely controlling both stability and sorting of the RNAs (Deng et al, 2020;McKenzie et al, 2016;Santangelo et al, 2016;Shurtleff et al, 2016;Villarroya-Beltri et al, 2013;Zietzer et al, 2020). We and others identified argonaute 2 (Ago2) and other RISC complex proteins as potent mediators of miRNA sorting into EVs (Bukong et al, 2014;Clancy et al, 2019;Mantel et al, 2016;McKenzie et al, 2016;Melo et al, 2014).…”
Section: Introductionmentioning
confidence: 77%
“…While RBPs are known to be important for the transport of RNAs into EVs (Leidal et al, 2020;Lin et al, 2019;Santangelo et al, 2016;Shurtleff et al, 2016;Villarroya-Beltri et al, 2013;Zietzer et al, 2020), it has been unclear how the RBP-RNA complexes are recruited to membranes for incorporation into EVs. Recent work has shown that two membraneless organelles that are comprised of RBP-RNA complexes -processing bodies and stress granules -form contacts with the ER (Lee et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the RNA transfer to specific cellular locations relies on RBPs, which can travel along the cytoskeleton ( Di Liegro et al., 2014 ; Eliscovich et al., 2013 ). RBPs, including HuR ( Mukherjee et al., 2016 ), hnRNP A2/B1( Villarroya-Beltri et al., 2013a ), hnRNPK ( Leidal et al., 2020 ), hnRNPU ( Zietzer et al., 2020 ), and scaffold-attachment factor B1(SAFB) ( Leidal et al., 2020 ), have been found to be involved in RNA packaging into EVs. Most of the current research is focused on the observation of this phenomenon and exploration of the mechanism, but very little research has been done to exploit these mechanisms as a tool for nucleic acid delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Two potential RNA selective sorting mechanisms have been proposed in mammals. First, miRNAs packaged into EVs were demonstrated to contain specific nucleotide motifs with which specific ribonucleoproteins interact to allow selective sorting [ 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 ]. Moreover, several membrane proteins involved in EV biogenesis are also involved in selective miRNA sorting [ 50 , 220 , 221 , 222 ].…”
Section: Mechanisms Of Rna Transfermentioning
confidence: 99%